A study on the laws relating to road accidents in Malaysia / Faten Hamamah Mohd Zaini...[et al.] - Mohd Zaini, Faten Hamamah; Ahmad Nazri, Nazatul Natasya; Ahmad, Nur Ayuni (Faculty of Law, 2013)
This research has been conducted to analyze the existing legal framework in Malaysia governing the traffic law relating to road accidents in Malaysia, where, special references have been made to the legal position in Australia and United Kingdom. This research aims to examine the adequacy in Malaysian law regarding the existing traffic law which still needs to be revised in certain areas in order to reduce the high rate of accident in Malaysia. This study focuses on the causes of the high rate accident and whether the law is adequate to deter people from committing traffic offence and thus reducing the accident rate. Therefore, this research aims to analyze abundance of issues regarding traffic laws such as the deterrence mechanism, the effectiveness of legislation, and the future approaches that can be taken to overcome this problem. It has been revealed throughout this study that even if the existing law is comprehensive, yet it will not be much of help it the existing law is poorly enforced. Furthermore, the use of educational programs and measures to cultivate the young minds and to change the cultural perception of the road users are also stressed in this research